Relative Risk Factors of Abnormal Endometrial Pathologies in Patients with Abnormal Uterine Bleeding - Suwanwanich M (Journal of The Department of Medical Services, 2019)
Objective: To evaluate the association of risk factor (s) with endometrial hyperplasia and carcinoma among women with abnormal uterine bleeding (AUB) at Ratchaburi Hospital. Method: A retrospective observational analytical cross-sectional study. The data was collected from patient record 270 patients who had undergone endometrial curettage due to AUB during 1st October 2016 to 30th September 2018. To study demographic data (age, BMI, underlying disease, parity and hormonal used) compared factors in normal endometrium (n=216) and abnormal endometrium (n=54). Result: Of 1,496 AUB patients, the prevalence in pre-menopause was 87.5% and post-menopause was 12.5%. AUB patients underwent endometrial curettage (18.05%). The most common endometrial pathology in pre-menopause AUB was proliferative endometrium (27.27%). Abnormal endometrial pathology in pre-menopause was found in 10.3%. The most common endometrial pathology in post-menopause was atrophic endometrium (40.01%). Abnormal endometrial pathology in post-menopause was found in 35.24%. Relative risk of endometrial hyperplasia and carcinoma in nulliparity, post-menopause, diabetes, metabolic syndrome, hypertension and obesity among women with AUB were 7.44, 4.74, 3.65, 3.57, 3.33 and 2.88 respectively. Conclusion: Nulliparity, post-menopause, diabetes, metabolic syndrome, hypertension and obesity have been significantly related to abnormal endometrial pathologies in patients with AUB.